Non-Sterilized Fermentation of 2,3-Butanediol with Seawater by Metabolic Engineered Fast-Growing Vibrio natriegens - Meng, Wensi; Zhang, Yongjia; Ma, Liting; Lü, Chuanjuan; Xu, Ping; Ma, Cuiqing; Gao, Chao (Frontiers in Bioengineering and Biotechnology, 2022)
Sustainable and environment-friendly microbial fermentation processes have been developed to produce numerous chemicals. However, the high energy input required for sterilization and substantial fresh water consumption restrict the economic feasibility of traditional fermentation processes. Vibrio natriegens is a promising microbial chassis with low nutritional requirements, high salt tolerance and rapid growth rate. In this study, V. natriegens was metabolic engineered to produce 2,3-butanediol (2,3-BD), an important platform chemical, through non-sterilized fermentation with seawater-based minimal medium. Under optimized fermentative conditions, 41.27 g/L 2,3-BD was produced with a productivity of 3.44 g/L/h and a yield of 0.39 g/g glucose by recombinant strain V. natriegensΔfrdAΔldhA-pETRABC. This study confirmed the feasibility of non-sterilized fermentation using seawater to replace freshwater and other valuable chemicals may also be produced though metabolic engineering of the emerging synthetic biology chassis V. natriegens.